Teaching compassion through a community-led, experiential learning activity for undergraduate medical students: The Empathy Project - Shoppoff, Lina; Mathew, Christine; Burkholder Harris, Kaite; Muldoon, Laura; Persaud, Sydney; Kelly-Langer, Sophia; Davidson, Elisha; Alie, Moira; Grondin, Carissa; Kendall, Claire E (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Implication StatementWe co-facilitated a mandatory community-led experiential learning activity for medical students with the Alliance to End Homelessness Ottawa that demonstrates the feasibility and positive impact of incorporating community-led learning into the medical school curriculum.